2020
DOI: 10.1192/j.eurpsy.2020.72
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and paliperidone palmitate antipsychotic combination in treatment-resistant schizophrenia and other psychotic disorders: A retrospective 6-month mirror-image study

Abstract: Background: Around 30% of patients with schizophrenia are considered treatment resistant (TRS). Only around 40% of TRS patients respond to clozapine. Long acting injectable antipsychotics could be a useful augmentation strategy for nonresponders. Methods: We conducted a multicenter, observational, naturalistic, retrospective, 6-month mirror-image study to evaluate the efficacy and tolerability of clozapine and paliperidone palmitate association in 50 patients with TRS and other psychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…Bioque et al 27 conducted a retrospective, 6-month mirror-image study involving 50 individuals diagnosed with schizophrenia or schizoaffective disorder (n = 46), delusional disorder (n = 2), and bipolar disorder (n = 2). All patients were using clozapine and paliperidone palmitate for a mean duration of 5.24 months.…”
Section: Resultsmentioning
confidence: 99%
“…Bioque et al 27 conducted a retrospective, 6-month mirror-image study involving 50 individuals diagnosed with schizophrenia or schizoaffective disorder (n = 46), delusional disorder (n = 2), and bipolar disorder (n = 2). All patients were using clozapine and paliperidone palmitate for a mean duration of 5.24 months.…”
Section: Resultsmentioning
confidence: 99%
“…When poor medication adherence, the severity of the episode, and the severity of relapse are considered, LAIs of antipsychotic agents may be a treatment of choice for this group of patients because poor adherence increases the risk of disease relapse. A study revealed that the use of PLAI in combination with clozapine is effective in treating patients with treatment-resistant schizophrenia [ 48 ]. Our study demonstrated that the year before enrolment, the LAI group had higher incidences of acute psychiatric ward admission and a higher number of emergency room visits than did the NLAI group.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis revealed that atypical antipsychotics combined with clozapine did not improve positive symptoms despite positively affecting negative and depressive symptoms [ 39 ]. However, in a recent multicenter investigation with long follow-up, clozapine augmentation with the atypical antipsychotic, paliperidone, has shown significant relief of symptoms, lower number of hospitalization, and improved functionality [ 40 ]. Finally, a consensus of treatment strategies for refractory schizophrenia patients was introduced by the TRRIP working group, where combinations of clozapine and atypical antipsychotics such as aripiprazole or amisulpride were recommended for refractory positive and mixed symptoms [ 33 ], in line with the current study findings.…”
Section: Discussionmentioning
confidence: 99%